Logical family a memoir - Maupin, Armistead 1944- (Doubleday, 2017)
In this long-awaited memoir, the beloved author of the bestselling Tales of the City series chronicles his odyssey from the old South to freewheeling San Francisco, and his evolution from curious youth to ground-breaking writer and gay rights pioneer
Keywords: Geschichte 1900-2000; Konservativismus; Homosexualität; Familie; USA; Maupin, Armistead; Authors, American / 20th century / Biography; Autobiographies; Autobiografie; Biografie